A novel SSR4 variant associated with congenital disorder of glycosylation: a case report and related analysis - Sun, Wenqiang; Jin, Xinyun; Zhu, Xueping (Frontiers in Genetics, 2024)
Introduction: Congenital disorders of glycosylation (CDG) refer to monogenetic diseases characterized by defective glycosylation of proteins or lipids causing multi-organ disorders. Here, we investigate the clinical features and genetic variants of SSR4-CDG and conduct a preliminary investigation of its pathogenesis. Methods: We retrospectively report the clinical data of a male infant with early life respiratory distress, congenital diaphragmatic eventration, cosmetic deformities, and moderate growth retardation. Peripheral blood was collected from the case and parents, genomic DNA was extracted and whole-exome sequencing was performed. The mRNA expression of SSR4 gene was quantified by Real-time Quantitative PCR. RNA sequencing analysis was subsequently performed on the case and a healthy child. Results: Whole-exome sequencing of the case and his parents' genomic DNA identified a hemizygous c.80_96del in SSR4, combined with the case's clinical features, the diagnosis of CDG was finally considered. In this case, the expression of SSR4 was downregulated. The case were present with 1078 genes downregulated and 536 genes upregulated. SSR4 gene expression was significantly downregulated in the case. Meanwhile, gene set enrichment analysis (GSEA) revealed that SSR4-CDG may affect hemostasis, coagulation, catabolism, erythrocyte development and homeostatic regulation, and muscle contraction and regulation, etc. Improvement of growth retardation in case after high calorie formula feeding and rehabilitation training. Conclusions: Our study expanded the SSR4-CDG variant spectrum and clinical phenotype and analyzed pathways potentially affected by SSR4-CDG, which may provide further insights into the function of SSR4 and help clinicians better understand this disorder.